ANALISIS KEMAMPUAN REPRESENTATIF MATEMATIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL TEOREMA PYTHAGORAS - Mayla Puspita Ningrum; Slamet Hw (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The purpose of this study was to determine the mathematical representation ability of eighth grade junior high school students on the Pythagorean theorem material based on 3 indicators, namely visual representation, symbolic representation, and verbal representation. This study used the subject of class VIII D students at SMP 1 Mejobo. This research method uses descriptive research method with a qualitative approach. The instrument used is a mathematical representation ability test instrument with the Pythagorean Theorem material. This study uses data analysis techniques in the form of data reduction, data presentation, and conclusions. The results obtained from the research are that the representation ability of students in solving the Pythagorean Theorem material questions still needs to be improved again, because the average percentage of students' representation abilities as a whole is 53.12% so that it is in the medium category. Judging from each indicator, the ability of visual representation is included in the high category with a total percentage of 73.12%. However, for the indicator of the ability of symbolic representation or mathematical expression, it is in the medium category with a percentage of 65.83% and the verbal representation ability of students is in the low category with a percentage of 19.37%.